Determinants of Financial Reporting Quality: The Role of Information Technology Moderation in Local Government - Vera Demayu Putri; La Ode Anto; Intihanah Intihanah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the influence of human resource competencies and internal control systems on the quality of local government financial statements, with the use of information technology as a moderation variable. The research was motivated by the inconsistency of previous research findings (research gap), where some studies proved the positive influence of competence and SPI on the quality of reports, while other studies showed that competence had no effect without adequate technological support. This research comes with the novelty of integrating agency theory, stewardship theory, and institutional theory and placing the use of information technology as a moderation variable that has not been tested simultaneously in one model, especially in the Eastern Indonesia region. The research was conducted on the Regional Apparatus Organization (OPD) of Baubau City with a population of 120 employees who carry out accounting or financial administration functions as respondents. The purposive sampling technique is used to ensure that respondents meet the criteria and have a deep understanding of the regional financial reporting process. The data analysis method uses a quantitative approach with Moderated Regression Analysis (MRA) through SPSS version 27. The results of the study show that the competence of human resources and SPI partially has a positive and significant effect on the quality of financial statements. The interaction test proves that the use of information technology significantly strengthens the influence of HR and SPI competencies on the quality of financial statements. The contribution of this research is to provide empirical evidence that synergy between competent apparatus, a robust control system, and efficient integration of information technology is able to optimize the quality of local government financial statements, while enriching the public sector accounting literature with a technology moderation model in the context of archipelago regional government that is rarely studied.